Kekuatan positive reinforcement dalam meningkatkan perilaku rawat diri pada pasien skizofrenia - Novil Cut Nizar (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
The research subjects were 24-year-old men diagnosed with schizophrenia with a spectrum of other specific schizophrenia and other psychotic disorders. The focus of the problem being intervened was self-care behaviour in terms of bathing and dressing. The intervention was carried out using a behavioristic approach through the Positive Reinforcement technique. The results of the intervention show that the Positive Reinforcement technique can improve self-care behaviour.